Metal–organic framework-based solid-state electrolytes for all solid-state lithium metal batteries: a review. Issue 28 (28th June 2022) - Wei, Tao; Wang, Zhimeng; Zhang, Qi; Zhou, Yanyan; Sun, Cheng; Wang, Mengting; Liu, Ye; Wang, Sijia; Yu, Zidong; Qiu, Xiangyun; Xu, Shoudong; Qin, Sai
Abstract : This work systematically reviewed recent progress of MOF-based solid electrolytes in all solid-state metal batteries which has rarely been summarized. Abstract : Recently, metal–organic frameworks (MOFs), as a new class of porous crystalline organic–inorganic hybrid materials, have commanded significant attention in the field of energy storage and conversion. This work systematically reviewed recent progress of MOF-based solid electrolytes in all solid-state metal batteries which has rarely been summarized, and three different systems are sectionalized, including (1) neat MOFs as Li-ion conductors; (2) MOFs loaded with ionic liquids as solid electrolytes; (3) MOFs as fillers in solid electrolytes. The advantages as well as the current or future problems of MOFs in different systems are summarized, and typical design strategies or development trends are proposed. We hope that it would provide meaningful guidance for MOF-based electrolytes.